A facile synthesis of Ag/Ag2O@TiO2 for toluene degradation under UV–visible light: Effect of Ag formation by partial reduction of Ag2O on photocatalyst stability. (March 2021) - Xue, Xiuling; Gong, Xiuwen; Chen, Xiaoyi; Chen, Bor-Yann
Abstract: In recent years, environmental pollution caused by volatile organic compounds (VOCs) has posed a great challenge to environmental protection. This first-attempt study provided a novel facile chemical precipitation-reduction method to construct Ag/Ag2 O@TiO2 (A/AO@TO) photocatalyst for the removal of gaseous toluene. The introduction of Ag in the presence of NaBH4 with N2 purging inhibited the passivation of Ag2 O and thus enhanced the stability of A/AO@TO. A/AO@TO exhibited outstanding photocatalytic performance toward gaseous toluene under different light sources like UV light, simulated sunlight and natural light, which were 99.3%, 48.3% and 28.5%, respectively. The superior photocatalytic performance could be attributed to the synergy effect of p-n heterojunction between Ag2 O and TiO2 and the surface plasmon resonance (SPR) effect of Ag, which facilitate the separation of charge carriers and thus suppress the recombination rate of them, and enhance the light response. The active species like ·OH, ·O2 − and h + were contributed to the excellent photocatalytic performance. The study provided a new method for the fabrication of A/AO@TO photocatalyst and introduce p-n scheme A/AO@TO as a feasible natural sunlight photocatalyst for further applications. Highlights: A/AO@TO was fabricated via a novel facile two-step precipitation-reduction method. Ag/Ag2 O system was used to promote the stability of Ag2 O under light irradiation. A/AO@TO showed a high efficiency toward toluene degradation on the continuous flow. Ag could not only improve light response but also act as a charge transfer bridge.